The Effect of Raw Materials Quality and Production Processes on Product Quality (Survey on Garuda Jaya Factory Ciamis Employees) - Ilyas Wahidin Mubarok; Suci Putri Lestari; Kusuma Agdhi Rahwana (Penerbit Jurnal Indonesia, 2022)
This study aims to determine the quality of raw materials and production processes on product quality on the products of Garuda Jaya Factory Ciamis skewers. The method used is causality with a quantitative approach. Data collection techniques are by interviewing and distributing questionnaires. The population and sample are 40 production employees using the saturated sample technique. The analysis software used is SPSS version 25. The analytical tool used is multiple linear regression. The results showed that the quality of raw materials and production processes simultaneously and partially had a significant positive effect on product quality on the products of Garuda Jaya Factory Ciamis skewers.